Pornografia de vingança : vulnerabilidades femininas e poder punitivo - Rodríguez, Liziane da Silva (2018)
This dissertation, which belongs to the research line “Violence, Crime and Security” of the Post-Graduate Program in Criminal Sciences, addresses the phenomenon of pornography from a criminological bias having as an anchor point a critical feminist perspective on punitive power. In this sense, an overview of the history of feminism is presented including its first accomplishments and discursive transformations. Focusing on revenge pornography, it is the objective of the study to demonstrate that the woman still remains as a product of male control from the angle of revenge and sexuality. Based on this observation, starting from a political-criminological approach, the analysis uncovers the punitive power as a selective and stigmatizing field and question its alleged "protection" in the confrontations of female vulnerabilities, more specifically on the complex a phenomenon under discussion that involves female sexual freedom.